BREEZE: Open‐label clinical study to evaluate the safety and tolerability of treprostinil inhalation powder as Tyvaso DPI™ in patients with pulmonary arterial hypertension. (7th April 2022) - Spikes, Leslie A.; Bajwa, Abubakr A.; Burger, Charles D.; Desai, Sapna V.; Eggert, Michael S.; El‐Kersh, Karim A.; Fisher, Micah R.; Johri, Shilpa; Joly, Joanna M.; Mehta, Jinesh; Palevsky, Harold I.; Ramani, Gautam V.; et al.
Abstract: Inhaled treprostinil is an approved therapy for pulmonary arterial hypertension (PAH) and pulmonary hypertension associated with interstitial lung disease in the United States. Studies have confirmed the robust benefits and safety of nebulized inhaled treprostinil, but it requires a time investment for nebulizer preparation, maintenance, and treatment. A small, portable treprostinil dry powder inhaler has been developed for the treatment of PAH. The primary objective of this study was to evaluate the safety and tolerability of treprostinil inhalation powder (TreT) in patients currently treated with treprostinil inhalation solution. Fifty‐one patients on a stable dose of treprostinil inhalation solution enrolled and transitioned to TreT at a corresponding dose. Six‐minute walk distance (6MWD), device preference and satisfaction (Preference Questionnaire for Inhaled Treprostinil Devices [PQ‐ITD]), PAH Symptoms and Impact (PAH‐SYMPACT®) questionnaire, and systemic exposure and pharmacokinetics for up to 5 h were assessed at baseline for treprostinil inhalation solution and at Week 3 for TreT. Adverse events (AEs) were consistent with studies of inhaled treprostinil in patients with PAH, and there were no study drug‐related serious AEs. Statistically significant improvements occurred in 6MWD, PQ‐ITD, and PAH‐SYMPACT. Forty‐nine patients completed the 3‐week treatment phase and all elected to participate in an optional extension phase. These results demonstrate that, in patients with PAH, transition from treprostinil inhalation solution to TreT is safe, well‐tolerated, and accompanied by statistically significant improvements in key clinical assessments and patient‐reported outcomes with comparable systemic exposure between the two formulations at evaluated doses (trial registration: clinicaltrials.gov identifier: NCT03950739).